Anticonvulsant activity of N(2'-propylpentanoyl)-2-pyrrolidinone and its effects on gamma-aminobutyric acid (gaba) levels in rat cerebral cortex - Chatchai Powthongchin (Chulalongkorn University, 2013)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1994